Convívio de estudantes na Cantina Universitária - Artur Pinto
1-Maria Otília (Letras); 2-João Sena (Direito); 3-Maria José Caeiro (?); 4-Santo Alfredo (Letras), 5-Joaquim Portilheiro (Letras); 6-Manuel Ramires (Direito); 7-João Feijão (Letras); 8-Leonor Arroio (Letras); 9-Manuela Calvet (Letras); 10-Ana Maria Alves (Letras); 11-Durão (?) (Direito); 12-Luisa Lemos (Letras); 13-Jorge Neto Valente (Direito); 14-Helena Bruto da Costa (Direito); 15-Maria João Seixas (Letras).